RESTORATIVE JUSTICE SEBAGAI PENDEKATAN PENYELESAIAN PERKARA PIDANA OLEH KEJAKSAAN RI - Rahman, Teuku (The Prosecutor Law Review, 2023)
The prosecutor's office in handling a criminal case can apply the concept of restorative justice where the process is aimed at the greatest benefit that can be felt by the parties involved. To implement a method for resolving criminal cases using a restorative justice principle approach, the legal substance, legal structure and legal culture must first be formulated in a criminal justice system work program that involves all elements of the criminal justice system so that it does not conflict with applicable procedural law norms. The application of restorative justice in resolving criminal cases in Indonesia can adopt the concept of Plea Bargainging and Deferred Prosecution Agreement which developed in England and the United States. The application of the concept of Plea Bargainging and Deferred Prosecution Agreement will take into account the confession and conviction of the perpetrator of the crime so that the sentence can then be reduced.